Impact of cannabinoids on cancer outcomes in patients receiving immune checkpoint inhibitor immunotherapy - Vigano, MariaLuisa; Wang, Lixing; As’sadiq, Alia; Samarani, Suzanne; Ahmad, Ali; Costiniuk, Cecilia T. (Frontiers in Immunology, 2025)
Cannabinoids relieve pain, nausea, anorexia and anxiety, and improve quality of life in several cancer patients. The immunotherapy with checkpoint inhibitors (ICIs), although very successful in a subset of patients, is accompanied by moderate to severe immune-related adverse events (ir-AE) that often necessitate its discontinuation. Because of their role in symptomatic relief, cannabinoids have been used in combination with immune checkpoint inhibitor (ICI) immunotherapy. A few studies strongly suggest that the use of medicinal cannabis in cancer patients attenuates many of the ir-AE associated with the use of ICI immunotherapy and increase its tolerability. However, no significant beneficial effects on overall survival, progression free survival or cancer relapses were observed; rather, some of the studies noted adverse effects of concurrent administration of cannabinoids with ICI immunotherapy on the clinical benefits of the latter. Because of cannabinoids’ well documented immunosuppressive effects mediated through the cannabinoid recptor-2 (CB2), we propose considering this receptor as an inhibitory immune checkpoint per se. A simultaneous neutralization of CB2, concurrent with cannabinoid treatment, may lead to better clinical outcomes in cancer patients receiving ICI immunotherapy. In this regard, cannabinoids such as cannabidiol (CBD) and cannabigerol (CBG), with little agonism for CB2, may be better therapeutic choices. Additional strategies e.g., the use of monoacylglycerol lipase (MAGL) inhibitors that degrade some endocannabinoids as well as lipogenesis and formation of lipid bilayers in cancer cells may also be explored. Future studies should take into consideration gut microbiota, CYP450 polymorphism and haplotypes, cannabinoid-drug interactions as well as genetic and somatic variations occurring in the cannabinoid receptors and their signaling pathways in cancer cells for personalized cannabis-based therapies in cancer patients receiving ICIs. This may lead to rational knowledge-based regimens tailored to individual cancer patients.